PUBLIC TRANSPORTATION SERVICES FROM THE PERSPECTIVE OF NEW PUBLIC SERVICES IN SIDOARJO REGENCY - Sangianto; Fatah , Zainal (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the implementation of public transportation services in Sidoarjo Regency through the lens of the New Public Service (NPS) perspective to identify barriers and drivers of service quality. Using a qualitative approach with a case study design, data were collected through in-depth interviews with the Transportation Agency, transportation managers, and users, as well as through direct observation and a review of policy documents. The results indicate that the implementation of NPS principles in Sidoarjo Regency remains partial and has not been fully integrated into bureaucratic practices. The local government tends to use a technocratic approach that is reactive and oriented toward administrative control rather than acting as a facilitator of public interest. Empirical findings indicate a lack of a regular public dialogue mechanism, resulting in the needs of specific groups such as students, industrial workers, and the elderly not being equitably accommodated in route and schedule planning. The public currently perceives low service quality due to limited fleet availability, irregular schedules, and a lack of integration between modes, which has triggered a shift in public preference toward private vehicles and app-based transportation. Furthermore, collaboration between stakeholders remains administrative in nature and has not yet reached a deep level of cooperation, while the complaint accountability system has not been implemented consistently and transparently. To improve these conditions, this study recommends a paradigm shift from a bureaucratic model to a participatory model that positions citizens as active partners. The Sidoarjo Regency Government needs to strengthen public deliberation spaces, build cross-sectoral collaborative governance, increase the capacity of human resources with service ethics, and develop a performance assessment system based on user satisfaction and real experiences. This transformation is crucial for creating a transportation system that is sustainable, inclusive, and responsive to the dynamics of Sidoarjo's community mobility. Keywords: New Public Services, Public Transportation, Sidoarjo Regency, Community Participation, Collaborative Governance.